2013
DOI: 10.1111/1440-1630.12043
|View full text |Cite
|
Sign up to set email alerts
|

Managing ‘Generation Y’ occupational therapists: Optimising their potential

Abstract: While there may be generational differences between therapists in the workplace, inclusive management styles may be the most appropriate management approach. Career guidance, facilitating creativity, increasing work responsibility and integrating new technologies like social networking into practice may be appropriate strategies for this staff group, to facilitate both their professional development and to retain them in the profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
1
18
1
2
Order By: Relevance
“…High effort and low reward lead to dissatisfaction and distress. 28,29 Recent evidence from research in health care professionals supports our findings: Hills et al 30 reported that Generation Y-workers (born 1982 to 2000) especially demand professional development opportunities. Another recent study revealed associations between job satisfaction and growth opportunity in nurses.…”
Section: Discussionsupporting
confidence: 84%
“…High effort and low reward lead to dissatisfaction and distress. 28,29 Recent evidence from research in health care professionals supports our findings: Hills et al 30 reported that Generation Y-workers (born 1982 to 2000) especially demand professional development opportunities. Another recent study revealed associations between job satisfaction and growth opportunity in nurses.…”
Section: Discussionsupporting
confidence: 84%
“…This population of young adults are also more inclined to be multitaskers, with a short attention span, and desire greater professional development compared to their older working age adult peers (Hills, Ryan, Warren‐Forward & Smith, ). Certainly, the study participants spoke favourably about wanting to develop new services, with some quickly gaining more senior positions, despite being a little older than the ‘Millennials’.…”
Section: Discussionmentioning
confidence: 99%
“…• Technologically-savvy (Allen, 2004;Bassett, 2008;Becton et al, 2014;Eisner, 2005;Hershatter & Epstein, 2010;Hills, Ryan, Warren-Forward, & Smith, 2013) • Highly educated (Allen, 2004;Eisner, 2005) • Praise-oriented (Espinoza & Ukleja, 2016;Tulgan, 2009) • Professionally mobile (Barkhuizen, 2014;Bassett, 2008;Becton et al, 2014;Du Plessis et al, 2015;Eisner, 2005;Twenge, 2010) Millennials also have been found to have certain preferences regarding their professional careers:…”
Section: The Millennial Generationmentioning
confidence: 99%
“…Unfortunately, industry is finding that talent management of Millennials is more difficult to accomplish than it was for preceding generations (Espinoza & Ukleja, 2016;Hershatter & Epstein, 2010;Hills et al, 2013;Tulgan, 2009). According to research, Millennials switch jobs more than any other generation before them (Barkhuizen, 2014;Bassett, 2008;Becton et al, 2014;Du Plessis et al, 2015;Kim & Barna Group, 2013;Twenge, 2010).…”
Section: The Millennial Generationmentioning
confidence: 99%